2020
DOI: 10.1074/mcp.r120.002234
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell Proteomics: Progress and Prospects

Abstract: MS-based proteome profiling has become increasingly comprehensive and quantitative, yet a persistent shortcoming has been the relatively large samples required to achieve an in-depth measurement. Such bulk samples, typically comprising thousands of cells or more, provide a population average and obscure important cellular heterogeneity. Single-cell proteomics capabilities have the potential to transform biomedical research and enable understanding of biological systems with a new level of granularity. Recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
241
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(243 citation statements)
references
References 74 publications
0
241
0
2
Order By: Relevance
“…In the area of lowinput proteomics, the field enjoys considerable excitement with early examples demonstrating proofof-principle of single-cell proteome analysis 16,33,37 . This is the combined result of miniaturized sample preparation, narrow-bore chromatography, and increased sensitivity in mass spectrometry, in conjunction with novel workflows such as TMT multiplexing with booster channels [38][39][40] . The fact that improved bioinformatics solutions have a major role to play in innovative single-cell strategies has remained underexposed, yet our data showed that re-analysis of an existing single-cell data set by IceR boosted the number of consistently quantified proteins from a few dozen to several hundreds.…”
Section: Discussionmentioning
confidence: 99%
“…In the area of lowinput proteomics, the field enjoys considerable excitement with early examples demonstrating proofof-principle of single-cell proteome analysis 16,33,37 . This is the combined result of miniaturized sample preparation, narrow-bore chromatography, and increased sensitivity in mass spectrometry, in conjunction with novel workflows such as TMT multiplexing with booster channels [38][39][40] . The fact that improved bioinformatics solutions have a major role to play in innovative single-cell strategies has remained underexposed, yet our data showed that re-analysis of an existing single-cell data set by IceR boosted the number of consistently quantified proteins from a few dozen to several hundreds.…”
Section: Discussionmentioning
confidence: 99%
“… 27 nanoPOTS demonstrate that reduction in sample volume and minimizing exposed surface areas is pivotal for sample recovery and achieves appropriate ratios between chemicals to the sample. Lysis and digestion conditions (i.e., enzyme to substrate ratio) optimized for bulk samples must be adapted to the extremely reduced protein concentration of single cells to ensure effective chemical lysis, improved digestion efficiency, and reduced autolysis 28,29 …”
Section: Sample Preparationmentioning
confidence: 99%
“…Unbiased measurement of transcripts, proteins, and metabolites in the live cell is the holy grail of molecular systems cell biology. Even today, after the invention of single-cell transcriptomics [1][2][3][4] , there exists no single technology capable of the unbiased characterization of both proteins and metabolites in the same single cell in vivo to enable the study of live organisms. While tools of molecular biology and high/super-resolution optical microscopy empowered systems biology for live organisms, they only work for a limited number of gene products at a time that also have to be known a priori, thus limiting research scope to targeted studies, typically building on prior knowledge.…”
Section: Textmentioning
confidence: 99%
“…Singlecell high-resolution mass spectrometry (HRMS) emerged as a powerful alternative for targeted as well as untargeted (discovery) studies (reviewed in refs. [1][2][4][5][6][7], yielding data to derive new hypotheses for biological investigations. Specialized technologies in cell handling, sample processing [8][9][10][11][12][13] , high-efficiency separations [14][15][16] , and ion generation equipped time-of-flight and orbitrap HRMS instruments with exquisite sensitivity.…”
Section: Textmentioning
confidence: 99%